2014
DOI: 10.1086/677198
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of growth and toxicity of a mixotrophic microbe: implications for understanding range expansion in Prymnesium parvum

Abstract: The rapid range expansion of the toxigenic marine haptophytic alga Prymnesium parvum in inland aquatic systems across the southern USA and beyond has prompted great interest in the ecology and evolutionary biology of this invasive bloom-forming species. Researchers have speculated that increased toxicity and heterotrophy in suboptimal environments allow blooms to develop in these new inland habitats that seem to represent extremes relative to P. parvum's perceived optimal niche. We used a laboratory-based stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…Not only were P. parvum growth rates during blooms in Lebanon Pool, Lake Texoma (Oklahoma-Texas) negatively related to temperatures between 7 1C and 16 1C, these blooms were large (up to 200 000 cells per ml) and quite toxic, as indicated by bioassays and large fish kills Zamor et al, 2014). In Hambright et al (2014), both growth rates and general toxicity in cultures were found to increase with increasing salinity.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Not only were P. parvum growth rates during blooms in Lebanon Pool, Lake Texoma (Oklahoma-Texas) negatively related to temperatures between 7 1C and 16 1C, these blooms were large (up to 200 000 cells per ml) and quite toxic, as indicated by bioassays and large fish kills Zamor et al, 2014). In Hambright et al (2014), both growth rates and general toxicity in cultures were found to increase with increasing salinity.…”
Section: Discussionmentioning
confidence: 97%
“…Because it is a microbial eukaryote that can occur in immense numbers, encyst and be passively transported, P. parvum's dispersal capabilities are potentially unlimited (sensu Finlay, 2002; but see Martiny et al, 2006;Hanson et al, 2012) and subjected to probabilities related to various potential vectors, such as wind, migratory-animal-assisted propagation or even human intervention (Johnson et al, 2008). For example, Hambright et al (2014) estimated that during a P. parvum bloom of 10 5 cells per ml in Lebanon Pool (volume B3 Â 10 6 m 3 ), the total P. parvum population would exceed 3 Â 10 11 individuals and represent an immense pool for downstream transport of invasive propagules via hydraulic flushing and advective downstream flow. Yet, P. parvum, which is often detected downstream, has yet to bloom in any area of the lake outside the environmental conditions identified here (Zamor et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although still presumably subjected to downstream transport of propagules from these large, sustained blooms, which can reach densities over 2 × 10 5 cells per mL, the rest of the lake has not experienced any establishment of P. parvum (defined as recurrent winter blooms). However, it is important to keep in mind that, before propagule exposure, we manipulated our microcosms' salinity levels to mimic those thought to be conducive to P. parvum establishment: i.e., ∼2 ppt (29,41), effectively creating a niche space for P. parvum. The role of salinity is particularly important, P. parvum being a marine species that is already at the limit of its salinity tolerance in this reservoir (41) and with most recorded blooms occurring when salinity exceeds 1.7 practical salinity units (psu) (29).…”
Section: Discussionmentioning
confidence: 99%